'Humanizing' healthcare environments: architecture, art and design in modern hospitals. Issue 1 (2nd January 2018) - Bates, Victoria
ABSTRACT: In recent decades, hospital design literature has paid increasing attention to an apparent need to 'humanize' hospital environments. Despite the prevalence of this design goal, the concept of 'humanizing' a space has rarely been defined or interrogated in depth. This article focuses on the meaning of humanization, as a necessary step towards understanding its implementation in practice. It explores the recent history of humanistic design as a goal in healthcare contexts, focusing on the UK in the late twentieth century. It shows that many features of humanistic design were not revolutionary, but that they were thought to serve a new purpose in counterbalancing high-technology, scientific and institutional medical practice. The humanistic hospital, as an ideal, operated as a symbol for wider social concerns about the loss – or decentring – of patients in modern medical practice. Overall, this article indicates a need to interrogate further the language of 'humanization' and its history. The term is not value free; it carries with it assumptions about the dehumanization of modern medicine, and has often been built on implicit binaries between the human and the technological.